Time Course of Brain Activity Changes Related to Number (Quantity) Processing Triggered by Digits Versus Number Words: An Event-Related Potential (ERP) Study - Peter Walla; Philipp Klimovic (Applied Sciences)
The neuroscience of language processing in the human brain has a long history. Strings of letters that form meaningful words trigger lexical and semantic processing, which in turn lead to conscious awareness of what the words mean. However, it is still unclear how the brain processes normal words differently from number words and, more interestingly, how the brain processes number words differently from digits, both of which are meant to trigger quantity processing. While much of the literature deals with this topic, the time course of the respective differences in brain activity has been largely ignored. This may be because most studies have used functional magnetic resonance imaging (fMRI), which is known to have limited temporal resolution. This study used electroencephalography (EEG), more specifically event-related potentials (ERPs), to investigate brain potential differences between visual presentations of words, non-words, number words and digits. This approach made it possible to describe the time course of brain activity evoked by these four stimulus categories. Starting at about 200 ms post-stimulus, digits elicited the strongest negative ERP in the right occipito-parietal cortical region. Peaking at around 300 ms after stimulus onset, number words elicited the most negative going ERP in the left occipito-parietal area. Finally, starting at about 400 ms after stimulus onset, digits elicited by far the most negative ERP in the left inferior fronto-temporal area. All of these findings are supported by analytical statistics across all study participants. It is noteworthy that the last effect in the left inferior fronto-temporal area can also be seen for number words, but it is much smaller and not statistically significant. In summary, we found clear differences between brain activity related to the processing of words, non-words, number words, and digits, providing evidence that the left inferior fronto-temporal cortical area is specialised for the processing of quantities. Furthermore, it can be concluded that digits are better symbols for mediating quantity processing in the human brain than number words.